Reed Solomon Coded Cooperation Scheme In Mobile Communication Networks And Application - AlMawgani, Abdulkarem Hussein Mohammed (2011)

(untitled)
Coded cooperative communication technique utilizes single antenna mobiles in a multi-user environment that share their antennas and incorporates channel coding in order to achieve transmit diversity. This thesis presents a new coded cooperation scheme based on Reed Solomon (RS) codes. The RS codes are very effective in correcting random symbol errors and random burst errors over wireless fading channels. The new coded cooperation system splits the data into two frames, using a mask vector arithmetic operation. The new scheme offers significant diversity gain improvement as compared to the renowned coded cooperation scheme that utilizes the Rate-Compatible Punctured Convolutional Code (RCPC). This work also derives the mathematical outage probability expressions for new RS coded cooperation scheme that proves its capacity to achieve full diversity gain.